Overview of the Impacts of Additive Production Techniques on the Environment: Production of Continuous Fibers, Direct Laser Sintering of Metals and Selective Laser Sintering Techniques - Potrč, Sanja; Bogataj, Miloš; Kravanja, Zdravko; Novak Pintarič, Zorka; Marina Bajić (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
Additive manufacturing (AM) has experienced significant growth in recent years, emerging as a transformative technology with broad applications across various industries. This review explores the advantages, disadvantages, and environmental impacts of AM, an important area of consideration as this technology continues to gain popularity. By analyzing existing literature, we assess the challenges associated with AM processes, particularly in comparison to traditional manufacturing methods. AM has the greatest potential to contribute to sustainable development by the production of lightweight components and complex industrial products with intricate designs. These products are made with minimal material usage. Consequently, also waste and emissions are reduced, which are significant environmental advantages. Overall, this review highlights the importance of AM as a tool for advancing sustainability in manufacturing and offers valuable insights for Continuous Fiber Fabrication, Direct Metal Laser Sintering, and Selective Laser Sintering techniques to enhance their competitive advantage while reducing their environmental impact.